The effects of mercury exposure on Amazonian fishes: An investigation of potential biomarkers - Vieira, José Cavalcante Souza [UNESP]; Braga, Camila Pereira; Queiroz, João Vitor de [UNESP]; Cavecci-Mendonça, Bruna [UNESP]; Oliveira, Grasieli de [UNESP]; Freitas, Natália Galvão de [UNESP]; Fernandes, Ana Angélica Henrique [UNESP]; Fernandes, Mileni da Silva; Buzalaf, Marília Afonso Rabelo; Adamec, Jiri; Zara, Luiz Fabrício; Padilha, Pedro de Magalhães [UNESP] (Elsevier, 2023)
Exposure to mercury can interfere with the expression of proteins and enzymes, compromise important pathways, such as apoptosis and glucose metabolism, and even induce the expression of metallothioneins. In this study, analytical techniques were used to determine the concentration of total mercury (THg) in muscle and liver tissue, protein pellets, and spots [using graphite furnace atomic absorption spectrometry (GFAAS)], and molecular techniques were used to identify metalloproteins present in mercury-associated protein spots. Thirty individuals from three different fish species, Cichla sp. (n = 10), Brachyplatystoma filamentosum (n = 10), and Semaprochilodus sp. (n = 10) from the Brazilian Amazon were used. Oxidative stress indicators [such as glutathione peroxidase (GSH-Px), catalase (CAT), superoxide dismutase (SOD), a marker of lipid peroxidation (LPO)] and the possible expression of metallothioneins in muscle and liver tissues were investigated. The two piscivorous species, Cichla sp. and B. filamentosum, presented the highest concentrations of mercury in their hepatic tissue, 1219 ± 15.00 and 1044 ± 13.6 μg kg−1, respectively, and in their muscle tissue, 101 ± 1.30 μg kg−1 and 87.4 ± 0.900 μg kg−1, respectively. The non-carnivorous species Semaprochilodus sp. had comparatively low concentrations of mercury in both its hepatic (852 ± 11.1 μg kg−1) and muscle (71.4 ± 0.930 μg kg−1) tissues. The presence of mercury was identified in 24 protein spots using GFAAS; concentrations ranged from 11.5 to 787 μg kg−1, and mass spectrometry identified 21 metal-binding proteins. The activities of GSH-Px, CAT, and SOD, related to oxidative stress, decreased proportionally as tissue Hg concentrations increased, while the levels of LPO markers increased, indicating the presence of stress. Our study results demonstrate possible mercury interference in oxidative stress markers (GSH-Px, CAT, SOD, and LPO), in addition to the identification of 21 metal-binding proteins as possible biomarkers of mercury exposure in fish.
Keywords: Mercury biomarkers; Metal-binding protein; Metalloproteomics; Metallothionein